Cheese bread rereading: Vegetarian version with olive flour - Santos, Carolina Dias dos; Menezes, Rafaella Câmara Rocha; Dal Bosco, Simone Morelo (Revista Verde de Agroecologia e Desenvolvimento Sustentável, 2021)
The olive tree (Olea europaea L.) is made up of leaves that can be consumed, but are usually discarded by mechanized harvesting. An alternative to enable the disposal of olive leaves is to prepare the olive leaf flour (FFO), making use of it. Thus, the objective of this research was to prepare a vegetarian cheese bread added with olive leaf flour in order to make a new alternative for the technological use of this residue feasible. Five cheese bread formulations were developed, changing the amount of flour from the olive leaves added (0.95 - 2.85%) and subjected to the evaluation of sensory characteristics by the method of Quantitative Descriptive Analysis. The results showed that, among the fifteen attributes evaluated, the herbaceous, bitter and cheese flavors together with the herbaceous aroma showed a significant difference. Among the attributes analyzed, the FFO contributed to the greater bitter taste of the cheese breads, followed by the herbaceous flavor and aroma. It was concluded that it was possible to prepare a vegetarian cheese bread added with olive leaf flour as an alternative for the technological use of this residue.